The Effect of Intravenous Ketamine in Suicidal Ideation of Emergency Department Patients - Kashani, Parvin; Yousefian, Shiva; Amini, Afshin; Heidari, Kamran; Younesian, Somaie; Hatamabadi, Hamid Reza (Archives of Academic Emergency Medicine, 2018)
Introduction: Suicidal ideation is an emergent problem in the Emergency Department (ED) that often complicates patient disposition and discharge. It has been shown that ketamine possesses fast acting antidepressant and anti-suicidal effects. This study was conducted to examine the effects of a single intravenous bolus of ketamine on patients with suicidal ideations in ED. Methods: Forty-nine subjects with suicidal ideations with or without an unsuccessful suicide attempt, received 0.2 mg/kg of ketamine. Scale for suicidal ideation (SSI) and Montgomery-Abserg depression-rating scale (MADRS) were evaluated before and 40, 80 and 120 minutes after drug intervention. The results were compared using the paired t-test and patients were followed up 10 days after ED admission for remnant suicide ideation. Results: SSI (df: 3, 46; F=80.7; p<0.001) and MADRS (df: 3, 46; F=87.2; p<0.001) scores significantly dropped after ketamine injection; the SSI score before and after 20, 40, and 80 minutes of ketamine injection were 23.0Â±6.7, 16.2Â±5.2, 14.3Â±4.3, and 13.6Â±4.0 respectively. The MADRS scores were 38.2Â±9.3, 25.6Â±7.1, 22.7Â±6.3, and 22.1Â±5.95 at the same time intervals. 25.5% of patients were hospitalized, 63.3% received medications and 12.2% discharged. 6.2% of patients had suicidal ideations ten days after ED disposition. Â Conclusion: It seems that Ketamine could not be a good choice for fast reduction of suicidal ideations in ED patients. Further studies are needed to determine the optimal dose of ketamine for different patients.